Genetic control of fiber yield and quality, and DNA marker development in kenaf (Hibiscus cannabinus L.) - Behmaram, Rahmatollah (2013)
The study was conducted to investigate the genetics of kenaf fiber yield and quality, and identify molecular markers associated with yield and fiber quality traits to facilitate marker-assisted breeding. This study was conducted in three stages. In stage one, two populations which served as base generations were generated, and genetic control and heritability of fiber yield and quality were studied using Analysis of Generation Means procedure. In stage two, kenaf genomic DNA extraction protocol was optimized and new Simple Sequence Repeats (SSR) and Single Nucleotide Polymorphism (SNP) markers were developed. Finally, in stage three, genotyping of individual plants of the F2 generation and marker-trait association analysis were conducted. Two sets of generations derived from 1X51 x Ghana07 and Gregg x Ghana07 crosses, i.e. the P1, P2, F1, F2, BC1.P1 and BC1.P2, were evaluated in a randomized complete block design with three replications. Analysis of generation means using weighted least squares procedure was performed on stalk dry weight, bast percentage, days to flowering, plant height, basal stalk diameter and middle stalk diameter. Analysis of generation means revealed that bast percentage was mainly controlled by dominance effects whereas stalk dry weight was mainly controlled by additive effects. Estimates of heterosis based on mid-parental values were generally high and ranged from 10 to 55% for stalk dry weight and bast percentage. Estimates of inbreeding depression, calculated from F1 and F2 generation means, were 55% for stalk dry weight in Population 1 (i.e. derived from 1X51 x Ghana07 cross) and 1.43% in Population 2 (i.e. derived from the Gregg x Ghana07 cross). Estimates of inbreeding depression for bast percentage were 5% in Population 1 and 15% in Population 2. DNA extraction protocol was optimized by adjustment of the cetyltrimethylammonium bromide (CTAB), polyvinylpyrrolidone (PVP) and 2-mercaptoethanol (2-ME) concentrations. The extraction buffer containing 14.3 mM 2-ME and 0.5% CTAB (w/v) produced high DNA quantity and quality. Among 72 SSR primer pairs, 42 primers could amplify fragments from kenaf genomic DNA. Alignment of sequences for templates produced by 15 primers from 1X51 and Ghana07 cultivars revealed Single Nucleotide Polymorphism (SNP). Linkage map was constructed using the marker segregation data obtained from HRM analysis. Ten markers were located in three linkage groups, while five markers were not assigned to any group. The linkage map contained three linkage groups with 419.3 cM genome coverage. For the first time, a QTL is detected and report in kenaf for days to flowering between SSR-kenaf-24 and AB242153 loci. The QTL that was associated with days to flowering could be useful in future marker assisted breeding studies. The results of this study indicated that, the portion of phenotypic variations, which is controlled by additive gene effects, was generally high for stalk dry weight. Thus, selection in the segregating generations would lead to significant improvement of fiber yield. Furthermore, new procedures of DNA extraction and HRM-SNP F2 genotyping developed in this study can expedite future kenaf breeding.